Pelayanan Bimbingan Mental dalam Membantu Keberfungsian Sosial Anak Berhadapan dengan Tindak Pidana Pelecehan Seksual - Willyantara, Anggi Putra; Prayitno, Hadi (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2021)
Sexual harassment is a problem that is no longer public. In ancient times the child who was the victim of adult sexual harassment, but today is precisely the child who is the perpetrator. The BAPAS of Class II Jember is a pranata with the main task of providing public guidance with the form of mental coaching to be able to increase confidence and social functioning back in the community. The problem of this research is how mental tutoring services help the child's social functioning be faced with criminal acts of sexual harassment. The study aims to describe mental tutoring services in helping the social functioning of children face the crime of sexual harassment. The study used a qualitative approach with descriptive type. Determination of informant with Purposive technique. Data collection techniques using non-participant observation, semi-structured interviews, and documentation. Data analysis techniques using data reduction, data display, and verification. The validity technique of data uses the triangulation source and method. The results of this study showed that advisers in the early stages of establishing relationships with clients, conducting assessment, intervening by determining the plan of guidance and Counseling program, monitoring and termination.